Indigenous Mathematics of Native North Americans. - DeCesare, Rich (2007)
Keywords: dept.mat; faculty_collection; sabbatical_report

Born This Day: A Book of Birthdays and Quotations of Prominent People Through the Centuries - Nowlan, Robert A. (McFarland & Co., 2007)
"For each date, a diverse dozen speakers were chosen based on prominence; the quality of the quotation; the uniqueness of the speaker with relation to gender, time period, nationality and vocation; and conflicting social, political, religious or philosophical background. Includes a quotation from each person that allows a glimpse of their personality"--Provided by publisher.
Keywords: Quotations, English; Birthday books; Literary calendars; dept.mat; faculty_collection

A Dictionary of Quotations in Mathematics - Nowlan, Robert A. (McFarland, 2002)
Keywords: Mathematics; Quotations, maxims, etc; dept.mat; faculty_collection

Doing Statistics for Business with Excel: Data, Inference, and Decision Making - Pelosi, Marilyn K.; Sandifer, Theresa M. (Wiley, 2002)
Keywords: Commercial statistics; Statistics; Industrial management; Statistical methods; dept.mat; faculty_collection

The Films of the Nineties: A Complete, Qualitative Filmography of Over 3000 Feature-Length English Language Films, Theatrical and Video-Only, Released Between January 1, 1990, and December 31, 1999 - Nowlan, Robert A. (McFarland, 2001)
Keywords: Catalogs; Motion pictures; dept.mat; faculty_collection

A Dictionary of Quotations and Proverbs About Cats and Dogs - Nowlan, Robert A.; Nowlan, Gwendolyn Wright (McFarland, 2001)
Keywords: Cats; Quotations, maxims, etc; Quotations, maxims, etc; Dogs; dept.ils; dept.mat; faculty_collection

A Dictionary of Quotations About Communication - Nowlan, Robert A.; Nowlan, Gwendolyn Wright (McFarland, 2000)
Keywords: Quotations; Quotations, English; dept.ils; dept.mat; faculty_collection

Art gallery theorems for guarded guards - Michael, T.S.; Pinciu, V. (Computational Geometry: Theory and Applications, 2003)
We prove two art gallery theorems in which the guards must guard one another in addition to the gallery. A set G of points (the guards) in a simple closed polygon (the art gallery) is a guarded guard set provided (i) every point in the polygon is visible to some point in G; and (ii) every point in G is visible to some other point in G. We prove that a polygon with n sides always has a guarded guard set of cardinality ⌊(3n-1)/7⌋ and that this bound is sharp (n5); our result corrects an erroneous formula in the literature. We also use a coloring argument to give an entirely new proof that the corresponding sharp function for orthogonal polygons is ⌊n/3⌋ for n≤6; this result was originally established by induction by Hernández-Peñalver. © 2003 Elsevier B.V.
Keywords: Art gallery theorems; Visibility in polygons; dept.mat

Polynomial identities of matrices with the symplectic involution: The low degrees - D'Amour, A.; Racine, M. (Communications in Algebra, 2004)
The *-polynomial identities of minimal degree of Mn(F) are determined for n = 2, 4, * the symplectic involution. Copyright © 2004 by Marcel Dekker, Inc.
Keywords: *-Polynomial identity; Polynomial identity; Symplectic involution; dept.mat

Full ideals - Hong, J.; Lee, H.; Noh, S.; Rush, D.E. (Communications in Algebra, 2009)
Contractedness of m-primary integrally closed ideals played a central role in the development of Zariski's theory of integrally closed ideals in two-dimensional regular local rings (R, m). In such rings, the contracted m-primary ideals are known to be characterized by the property that I: m = I: x for some x ∈ m\m2. We call the ideals with this property full ideals and compare this class of ideals with the classes of m-full ideals, basically full ideals, and contracted ideals in higher dimensional regular local rings. The m-full ideals are easily seen to be full. In this article, we find a sufficient condition for a full ideal to be m-full. We also show the equivalence of the properties full, m-full, contracted, integrally closed, and normal, for the class of parameter ideals. We then find a sufficient condition for a basically full parameter ideal to be full. © Taylor & Francis Group, LLC.
Keywords: Basically full ideal; Contracted ideal; Full ideal; Ideal with Rees property; Integrally closed ideal; dept.mat; m-Full ideal

Adaptive urn designs for estimating several percentiles of a dose–response curve - Mugno, Raymond; Zhus, Wei; Rosenberger, William F (Statistics in Medicine, 2004)
Dose-response experiments are crucial in biomedical studies. There are usually multiple objectives in such experiments and among the goals is the estimation of several percentiles on the dose-response curve. Here we present the first non-parametric adaptive design approach to estimate several percentiles simultaneously via generalized Pó lya urns. Theoretical properties of these designs are investigated and their performance is gaged by the locally compound optimal designs. As an example, we re-investigated a psychophysical experiment where one of the goals was to estimate the three quartiles. We show that these multiple-objective adaptive designs are more efficient than the original single-objective adaptive design targeting the median only. We also show that urn designs which target the optimal designs are slightly more efficient than those which target the desired percentiles directly. Guidelines are given as to when to use which type of design. Overall we are pleased with the efficiency results and hope compound adaptive designs proposed in this work or their variants may prove to be a viable non-parametric alternative in multiple-objective dose-response studies. Copyright © 2004 John Wiley & Sons, Ltd.
Keywords: *Dose-Response Relationship, Drug; Adaptive design; Dose-Response Relationship, Drug; Dose-response experiment; Generalized Pólya urn; Guidelines; Guidelines as Topic; Likelihood Functions; Monte Carlo method; Non-parametric design; Psychophysics; United States; article; biostatistics; c-optimal design; cerebrovascular accident; clinical trial; dept.mat; dose response; experimental design; human; kinesthesia; maximum likelihood method; neurologic disease; nonparametric test; process optimization; psychophysics; sensory stimulation; statistical analysis; theoretical study; validation process

Dominating Sets for Outerplanar Graphs - Pinciu, Val (International Conference on Applied Mathematics, 2004)
Abstract:- We provide lower and upper bounds for the domination numbers and the connected domination numbers for outerplanar graphs. We also provide a recursive algorithm that finds a connected domination set for an outerplanar graph. Finally, we show that for outerplanar graphs where all bounded faces are 3-cycles, the problem of determining the connected domination number is equivalent to an art gallery problem, which is known to be NP-hard. Key-Words:- dominating sets, star forests, outerplanar graphs, art gallery 1
Keywords: dept.mat; ⛔ No DOI found

A coloring algorithm for finding connected guards in art galleries - Pinciu, Val (Springer Verlag, 2003)
In this paper we consider a variation of the Art Gallery Problem. A set of points script G sign in a polygon Pn is a connected guard set for Pn provided that is a guard set and the visibility graph of the set of guards script G sign in Pn is connected. We use a coloring argument to prove that the minimum number of connected guards which are necessary to watch any polygon with n sides is ⌊(n - 2)/2⌋. This result was originally established by induction by Hernández-Peńalver [3]. From this result it easily follows that if the art gallery is orthogonal (each interior angle is 90° or 270°), then the minimum number of connected guards is n/2 - 2. © Springer-Verlag Berlin Heidelberg 2003.
Keywords: Algorithms; Art gallery; Artificial intelligence; Coloring algorithms; Computer science; Computers; Visibility graphs; dept.mat

Connected guards in orthogonal art galleries - Pinciu, Val (Springer Verlag, 2003)
In this paper we consider a variation of the Art Gallery Problem for orthogonal polygons. A set of points in a polygon Pn is a connected guard set for Pn provided that is a guard set and the visibility graph of the set of guards in Pn is connected. The polygon P n is orthogonal provided each interior angle is 90° or 270°. First we use a coloring argument to prove that the minimum number of connected guards which are necessary to watch any orthogonal polygon with n sides is n/2-2. This result was originally established by induction by Hernández-Peñalver. Then we prove a new result for art galleries with holes: we show that n/2-h connected guards are always sufficient to watch an orthogonal art gallery with n walls and h holes. This result is sharp when n = 4h + 4. We also construct galleries that require at least n/2-h-1 connected guards, for all n and h. © Springer-Verlag 2003.
Keywords: Art gallery; Art gallery problem; Geometry; New results; Visibility graphs; Watches; dept.mat

Computer-generated fractals using iterated function systems - Stiegler, Cynthia Joy Gayda (2003)
Keywords: dept.mat

College and university academic and professional appointments - Nelson, C; Conklin, CL; Galloway, R; Grant, KE; Halpern, J; Humphreys, RM; Kalman, L; Matthews, TE; Moore, RK; Smith, LD; Wood, DD (Academe-Bulletin of the Aaup, 2002)
Keywords: dept.mat

Numerical testing of the stability of viscous shock waves - Brin, Leon Q (Mathematics of Computation, 2001)
A new theoretical Evans function condition is used as the basis of a numerical test of viscous shock wave stability. Accuracy of the method is demonstrated through comparison against exact solutions, a convergence study, and evaluation of approximate error equations. Robustness is demonstrated by applying the method to waves for which no current analytic results apply (highly nonlinear waves from the cubic model and strong shocks from gas dynamics). An interesting aspect of the analysis is the need to incorporate features from the analytic Evans function theory for purposes of numerical stability. For example, we find it necessary, for numerical accuracy, to solve ODEs on the space of wedge products.
Keywords: dept.mat

Multiply guarded guards in orthogonal art galleries - Michael, T S; Pinciu, Val (Springer Verlag, 2001)
We prove a new theorem for orthogonal art galleries in which the guards must guard one another in addition to guarding the polygonal gallery. A set of points G in a polygon Pn is a k-guarded guard set for Pn provided that (i) for every point x in Pn there exists a point w in G such that x is visible from w; and (ii) every point in G is visible from at least k other points in G: The polygon Pn is orthogonal provided each interior angle is 90° or 270°. We prove that for k ≥ 1 and n ≥ 6 every orthogonal polygon with n sides has a k-guarded guard set of cardinality (Formula Presented.) this bound is best possible. This result extends our recent theorem that treats the case k = 1. © Springer-Verlag Berlin Heidelberg 2001.
Keywords: Art gallery; Cardinalities; Computation theory; Geometry; dept.mat

Realistic reconfiguration of crystalline (and telecube) robots - Aloupis, Greg; Collette, Sebastien; Damian, Mirela; Demaine, Erik D; Elkhechen, Dania; Flatland, Robin; Langerman, Stefan; Orourke, Joseph; Pinciu, Val; Ramaswami, Suneeta; Sacristan, Vera; Wuhrer, Stefanie (2009)
In this paper we propose novel algorithms for reconfiguring modular robots that are composed of n atoms. Each atom has the shape of a unit cube and can expand/contract each face by half a unit, as well as attach to or detach from faces of neighboring atoms. For universal reconfiguration, atoms must be arranged in 2×2×2 modules. We respect certain physical constraints: each atom reaches at most unit velocity and (via expansion) can displace at most one other atom. We require that one of the atoms can store a map of the target configuration. Our algorithms involve a total of O(n 2) such atom operations, which are performed in O(n) parallel steps. This improves on previous reconfiguration algorithms, which either use O(n 2) parallel steps [8,10,4] or do not respect the constraints mentioned above [1]. In fact, in the setting considered, our algorithms are optimal, in the sense that certain reconfigurations require Ω(n) parallel steps. A further advantage of our algorithms is that reconfiguration can take place within the union of the source and target configurations. © 2009 Springer-Verlag.
Keywords: Algorithms; Atoms; Novel algorithm; Physical constraints; Reconfiguration algorithm; Robotics; Robots; Target configurations; dept.mat

Exploring gender differences in the relationship between HIV/STD testing and condom use among undergraduate college students - Bontempi, Jean M Breny; Mugno, Raymond; Bulmer, Sandra Minor; Danvers, Karina; Vancour, Michele (American journal of health education, 2009)
Keywords: dept.mat; dept.pch

The signature of the chern coefficients of local rings - Ghezzi, Laura; Hong, Jooyoun; Vasconcelos, Wolmer V (Mathematical Research Letters, 2009)
This paper considers the following conjecture: If R is an unmixed, equidimensionallocal ring that is a homomorphic image of a Cohen-Macaulay local ring, then for any ideal J generated by a system of parameters, the Chern coefficient e1(J) < 0 is equivalent to R being non Cohen-Macaulay. The conjecture is established if R is a homomorphic image of a Gorenstein ring, and for all universally catenary integral domains containing fields. Criteria for the detection of Cohen-Macaulayness in equi-generated graded modules are derived. © International Press 2009.
Keywords: dept.mat; ⚠️ Invalid DOI

Leveraging summative assessment for formative purposes. - Vaden-Goad, Robert E (College Teaching, 2009)
The problem of motivation has received a great deal of attention, and many successful approaches have been developed. However, in areas such as introductory college mathematics, students often question their own potential for success. At the first sign of trouble, their fears are confirmed and many of them drop out, formally or informally. If a method could be found to improve persistence, motivational techniques would have an opportunity to succeed. In this article, the author describes a simple method to improve persistence using assessments that are normally already in place. Data are presented indicating that the method improves persistence and achievement. © 2009, Copyright Taylor & Francis Group, LLC.
Keywords: classroom assessment; dept.mat; mathematics

On the homology of two-dimensional elimination - Hong, Jooyoun; Simis, Aron; Vasconcelos, Wolmer V (Journal of Symbolic Computation, 2008)
We study birational maps with empty base locus defined by almost complete intersection ideals. Birationality is shown to be expressed by the equality of two Chern numbers. We provide a relatively effective method for their calculation in terms of certain Hilbert coefficients. In dimension 2 the structure of the irreducible ideals-always complete intersections by a classical theorem of Serre-leads by a natural approach to the calculation of Sylvester determinants. We introduce a computer-assisted method (with a minimal intervention by the computer) which succeeds, in degree ≤5, in producing the full sets of equations of the ideals. In the process, it answers affirmatively some questions raised by Cox [Cox, D.A., 2006. Four conjectures: Two for the moving curve ideal and two for the Bezoutian. In: Proceedings of Commutative Algebra and its Interactions with Algebraic Geometry, CIRM, Luminy, France, May 2006 (available in CD media)]. © 2007 Elsevier Ltd. All rights reserved.
Keywords: Almost complete intersection; Birational map; Elimination; Rees algebra; Special fiber; Sylvester determinant; dept.mat

On the fewest nets problem for convex polyhedra - Pinciu, Val (2007)
Given a convex polyhedron with n vertices and F faces, what is the fewest number of pieces, each of which unfolds to a simple polygon, into which it may be cut by slices along edges? Shephard's conjecture says that this number is always 1, but it's still open. The fewest nets problem asks to provide upper bounds for the number of pieces in terms of n and/or F. We improve the previous best known bound of F/2 by proving that every convex polyhedron can be unfolded into no more than 3F/8 non-overlapping nets. If the polyhedron is triangulated, the upper bound we obtain is 4F/11.
Keywords: Computational geometry; Convex polyhedrons; Simple polygon; Upper Bound; dept.mat; ⛔ No DOI found

Guarding the guards in art galleries - Michael, T S; Pinciu, Val (Math Horizons, 2006)
Keywords: dept.mat